ASSISTANCE IN THE APPLICATION OF THE ARTIFICIAL INTELLIGENCE PARAPHRASING TOOL "QUILLBOT" IN ARTICLE WRITING - Muzdalifah, Indah; Toresa, Dafwen; Wiza, Fana; Farwitawati, Reni (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
Writing is a fundamental skill for writers, researchers, lecturers, and students, especially in academic contexts where clarity, structure, and proper referencing are essential. Beyond composing coherent sentences, academic writing demands the ability to integrate references ethically and effectively. One key technique is paraphrasing—rephrasing others’ ideas in one’s own words while preserving the original meaning. This requires linguistic precision and conceptual understanding, yet many educators still struggle with it. Recognizing this challenge, the Community Service (PKM) team initiated a program titled Assistance in the Application of Artificial Intelligence Paraphrasing Tool Technology “Quillbot. The initiative aimed to introduce and train educators in using Quillbot, an AI-powered tool designed to support ethical and plagiarism-free paraphrasing in scientific writing. Delivered through a participatory approach, the training combined theoretical insights with hands-on practice. The results were impactful: 70% of participants had never used Quillbot before, highlighting the program’s success in expanding technological literacy. All participants found the tool helpful in improving writing efficiency and language quality. Many felt newly motivated to write, citing increased confidence and productivity. Beyond technical skills, the program fostered ethical awareness in writing practices. Overall, this initiative significantly contributed to promoting responsible and effective use of AI in education.